Pengaruh E-Trust dan E-Service Quality terhadap Repurchase Intention E-Commerce Shopee pada Mahasiswa di Kota Medan - Danise Ramadhani; Vivianti Novita; Desri Wiana; Edi Putra Berutu; Djames Siahaan (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
E-trust has an important role for consumers because especially transactions carried out by consumers through the Marketplace (online) have quite high potential risks compared to offline purchases, e-service quality indirectly provides customersatisfaction so that if consumers feel satisfied they will want to buy again will alsoincrease. The research method used is a quantitative research method. Sampling was carried out using incidental sampling technique with a total of 96 respondents and data collection was carried out by distributing questionnaires. The data analysis technique used is multiple linear regression using SPSS version 22 statistics. The research results show was e-trust has an effect on repurchase intention with a t value of 6.050 and a significance value of 0.000, e-service quality has an effect on repurchase intention with a tcount value of 6.505 and a significance value of 0.000, simultaneously e-trust and e-service quality influence repurchase intention with a fcount of 241.902 and a significance value of 0.000, the adjusted R square coefficient of determination test result is 0.835 which means that 83, 5% of Shopee e- commerce repurchase intention is influenced by e-trust and e-service quality while the remaining 16.5% repurchase intention isinfluenced by other variables not examined in this research.